2006
DOI: 10.1016/j.jacc.2005.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Microvolt T-Wave Alternans and the Risk of Death or Sustained Ventricular Arrhythmias in Patients With Left Ventricular Dysfunction

Abstract: Among patients with heart disease and LVEF < or =0.40, MTWA can identify not only a high-risk group, but also a low-risk group unlikely to benefit from ICD prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
210
2
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(222 citation statements)
references
References 36 publications
4
210
2
6
Order By: Relevance
“…However, their patients had a similar 2-year event rate to that reported in MUSTT (5), and comparable age, LVEF, incidence of QRS widening (≈30%) and 2-year event rates to those in recent TWA trials (14,21). Thus, differences in the incidence of non-sustained VT (required by Morin et al (17), unreported in prior TWA trials (14,21)), syncope (more common in the Ohio/Michigan study (14)), symptomatic heart failure and usage of angiotensin converting-enzyme or angiotensin receptor blockers are of unclear significance.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…However, their patients had a similar 2-year event rate to that reported in MUSTT (5), and comparable age, LVEF, incidence of QRS widening (≈30%) and 2-year event rates to those in recent TWA trials (14,21). Thus, differences in the incidence of non-sustained VT (required by Morin et al (17), unreported in prior TWA trials (14,21)), syncope (more common in the Ohio/Michigan study (14)), symptomatic heart failure and usage of angiotensin converting-enzyme or angiotensin receptor blockers are of unclear significance.…”
supporting
confidence: 64%
“…In addition, Morin et al (17) continued beta-blockers during TWA testing, that may theoretically attenuate TWA and impair its NPV (13). On the other hand, recent TWA trials reported high NPV for TWA either with (21) or without (14) continued betablockade during testing. Finally, exercise-TWA may be superior to TWA from atrial pacing (as used by Morin et al (17)), although this may influence the NPV less than other parameters (28).…”
mentioning
confidence: 99%
“…The microvolt T-wave alternans (MTWA) test is a promising noninvasive test that predicts arrhythmic risk and mortality both in patients with cardiac dysfunction and in patients with preserved LVEF (12,13). Although TWA is not traditionally considered to reflect structural heart disease, there is evidence that TWA reflects arrhythmic susceptibility related to structural nonuniformities (14).…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation for MTWA performance in Grimm 21 compared to the other studies of MTWA in DCM patients might be that in Grimm beta-blockers were withheld for at least 24 hours prior to MTWA testing while 74% of patients took beta-blockers during follow-up. In contrast in ALPHA 7 , Kitamura 3 , and Bloomfield 5 were not withheld prior to MTWA testing. It is known that beta-blockers both reduce the incidence of ventricular tachyarrhythmias andparticularly in patients with non-ischemic cardiomyopathy -suppress MTWA 22,23 .…”
Section: Mtwa In Non-ischemic Dilated Cardiomyopathy Patientsmentioning
confidence: 99%
“…Many studies conducted in patients without implanted ICDs have found MTWA to be a highly accurate risk stratifier and, in particular, have found that the rate of ventricular tachyarrhythmic events (VTEs) among patients who test MTWA negative is exceedingly low [1][2][3][4][5][6][7] suggesting that ICD therapy may not benefit such patients 8 . As a result, MTWA has been proposed as a means of guiding implantable cardioverter defibrillator (ICD) therapy in patients with risk factors for SCD but without a prior history of sustained VTEs (primary prevention patients).…”
Section: Introductionmentioning
confidence: 99%